Optimalisasi Hukum Untuk Hak-Hak Perlindungan Anak Buah Kapal Migran Dan Memberantas Agensi Ilegal - Putri Galuh Pitaloka; Ravikah Amelia; Reva Fitri Ramadhani; Leon Leon; Amanda Mutiara Natasya (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This article explores efforts to optimise the rights of crew in the international maritime contextand take a stand against illegal agency practices that harm them. An in-depth analysis of the ship's crew working conditions reveals labour rights violations and unsafe working conditions. Meanwhile, the role of illegal agents exacerbates the situation. This research urges the government to optimise the rights of migrant ship crew members. By detailing basic rights such as a living wage, safe working conditions, the research investigates the positive impact of implementing migrant worker protection policies. Focus is also given to countering illegal agents by identifying prevention and enforcement strategies that can be implemented. This research provides a foundation for cooperation between governments, shipping companies and international organisations to create a fair and sustainable maritime environment and eradicate illegal agencies that only want to benefit themselves. This research not only describes the challenges, but also illustrates solutions in protecting the rights of ship’s crew members and countering illegal agents in the maritime sector.